Narratives of women's sexual identity development: A collaborative inquiry with implications for rewriting transformative learning theory. - Ann K. Brooks; Kathleen Edwards (Adult Education Research Conference, 1997)
Transformative learning theory has attended primarily to cognition and our capacity to understand experience in terms of increasingly inclusive, discriminating, permeable, and integrative perspectives (Mezirow, 1991). However, it does not allow for an understanding of the intersubjective nature of meaning-making, nor does it address the workings of oppression or how learning occurs in relation to oppression. Thus, the purpose of this paper is to rewrite transformative learning to allow us to theorize the integration of the individual with the socio-historical and to enable the understanding of the relationship between individuals and social change.